2022
DOI: 10.3390/nano12030423
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Melting Duration of a PV/PCM System Integrated with Different Metal Foam Configurations for Thermal Energy Management

Abstract: The melting duration in the photovoltaic/phase-change material (PV/PCM) system is a crucial parameter for thermal energy management such that its improvement can realize better energy management in respect to thermal storage capabilities, thermal conditions, and the lifespan of PV modules. An innovative and efficient technique for improving the melting duration is the inclusion of an exterior metal foam layer in the PV/PCM system. For detailed investigations of utilizing different metal foam configurations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 36 publications
(50 reference statements)
0
4
0
Order By: Relevance
“…The inner, middle, and outer pipe diameters are 40, 80, and 120 mm, respectively, while the tube length is 250 mm. Note that the dimensions of the unit are considered based on the literature ( Al-Najjar et al, 2022 ; Chen et al, 2022 ).…”
Section: System Descriptionmentioning
confidence: 99%
“…The inner, middle, and outer pipe diameters are 40, 80, and 120 mm, respectively, while the tube length is 250 mm. Note that the dimensions of the unit are considered based on the literature ( Al-Najjar et al, 2022 ; Chen et al, 2022 ).…”
Section: System Descriptionmentioning
confidence: 99%
“…The boundary conditions and dimensions of the system are also indicated for the system with no fins. Note that the dimensions of the unit are considered based on the literature ( Al-Najjar et al, 2022 ; Chen et al, 2022 ).…”
Section: System Descriptionmentioning
confidence: 99%
“…Using phase change material (PCM) between cells can overcome the problem of large temperature difference between cells [29,30]. Wilke et al [31] demonstrated that incorporating PCM between battery cells can effectively mitigate temperature rise and temperature variation within battery modules.…”
Section: Introductionmentioning
confidence: 99%